2009
DOI: 10.1542/peds.2008-3388
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Auto-injectors: Is Needle Length Adequate for Delivery of Epinephrine Intramuscularly?

Abstract: The needle on epinephrine auto-injectors is not long enough to reach the muscle in a significant number of children. Increasing the needle length on the auto-injectors would increase the likelihood that more children receive epinephrine by the recommended intramuscular route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 11 publications
0
48
1
4
Order By: Relevance
“…As important, when drug manufacturers package needles with IM injectable medication, they must guide practice by providing appropriately sized needles according to various BMIs or weights of patients. [19,43] …”
Section: Reporting Of Methodological Datamentioning
confidence: 99%
See 2 more Smart Citations
“…As important, when drug manufacturers package needles with IM injectable medication, they must guide practice by providing appropriately sized needles according to various BMIs or weights of patients. [19,43] …”
Section: Reporting Of Methodological Datamentioning
confidence: 99%
“…The typical needles used in these injectors are often too short to reach muscle in heavier populations, including women and children. [11,29] Manufacturers recommending or providing appropriately sized needles to reach the target tissue is important to ensure efficacy of the medications and vaccines.…”
Section: Injection Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18] Studies in adult have shown the inadequacy of the epinephrine auto-injector needle length especially in women.…”
Section: Discussionmentioning
confidence: 99%
“…During an anaphylactic emergency, not only it is important that adrenaline is administered into the correct tissue compartment [15,16] but also that the correct dose of adrenaline is administered to achieve the desired clinical benefit.…”
mentioning
confidence: 99%